Genome-wide association mapping of bread wheat genotypes using yield and grain morphology-related traits under different environments - Ahmed, Hafiz Ghulam Muhu-Din; Zeng, Yawen; Khan, Muhammad Ahsan; Rashid, Muhammad Abdul Rehman; Ameen, Muhammad; Akrem, Ahmed; Saeed, Amjad (Frontiers in Genetics, 2023)
The depleting water resources and rise in global temperature due to climate change are the major challenges to agriculture and food security worldwide. Deciphering the underlying mechanisms of grain development and yield contributing traits are essential to develop climate resilient cultivars. Therefore, 105 bread wheat genotypes were assessed for a genome-wide association study (GWAS) using a 90k SNPs arrays, which was grown under control, drought, and heat stressed conditions for two crop seasons. The genotypes exhibited significant differences for traits under all environmental conditions. Highly significant variation was observed, with moderate (50.09%) to high (76.19%) heritability in the studied germplasm. A significant positive correlation existed among all studied traits. A total of 541 significant associations between marker and trait (MTAs) were found at P ≤ 10-3 after crossing FDR < 0.05 threshold for all traits. Out of these, 195, 179 and 167 significant MTAs were detected under control, drought, and heat-stressed conditions, respectively. Under control and drought conditions, the pleiotropic loci were observed as BS00010616_51 and BS00010868_51 on chromosomes 7B and 1B situated at 186.24cM 35.47cM, respectively. The pleiotropic locus (BS00010868_51, Kukri_c11154_1723, and Ex_c10068_1509) were identified on chromosomes 1B, 5B, and 2A, respectively, under control and heat stress. A stable and consistent locus (Excalibur_c20796_395) at chromosome 7A, located at 372.34cM, was also linked with grain morphology and yield-related attributes in control, drought, and heat-stressed conditions. The current investigation confirmed several previously reported MTAs for the traits under consideration and discovered new MTAs under harsh climatic circumstances. Identified SNPs will aid in the discovery of novel genes in wheat. Significantly associated SNPs would be utilized in marker-assisted selection and allowing for the development of drought and heat-tolerant genotypes with high yield to address global food security concerns